The sensory gene repertoire of deep-sea hydrothermal shrimp - Thomas Chertemps; Nicolas Montagné; Adrien Mathou; Nelly Léger; Magali Zbinden; Juliette Ravaux (PLoS ONE, 2026)
Deep-sea hydrothermal vents are among the most extreme and geochemically dynamic environments on Earth, characterized by steep gradients in temperature and chemical concentration. Alvinocaridid shrimp dominate the macrofaunal biomass at these sites and rely on their sensory systems to navigate these dark habitats. In this study, we provide the first comprehensive characterization of sensory gene repertoires associated with chemical and thermal detection in four deep-sea shrimp species occupying different ecological niches at hydrothermal vents on the Mid-Atlantic Ridge: Rimicaris exoculata , Rimicaris chacei , Mirocaris fortunata , and Alvinocaris markensis . Through de novo transcriptome assembly of sensory organs, we identified a great expansion of the variant Ionotropic Receptor (IR) family. Notably, we annotated 442 candidate IR transcripts in R. exoculata , the largest repertoire documented in any decapod crustacean. This expansion is primarily driven by the IR40a clade, suggesting adaptive radiation centred on the detection of the complex chemical waterscape of vents. Furthermore, we have identified a diverse set of Transient Receptor Potential (TRP) channels, including 18 TRPA genes in R. exoculata , which likely facilitate fine-tuned thermosensation in a high-gradient environment. In contrast, Chemosensory Proteins and Niemann-Pick type C2 proteins exhibited ubiquitous expression patterns, suggesting broader physiological roles beyond olfaction. These findings offer insights into the molecular adaptations that enable Alvinocarididae to thrive in the deep sea.